Pengaruh Tekanan Kompaksi Panas Satu-Arah Terhadap Karakteristik Komposit Phenolic Resin Diperkuat Serbuk Logam dan Boiler Fly-Ash - Devrin Dwiki Saputra; Sukanto Sukanto; Zaldy Sirwansyah Suzen (Jurnal Inovasi Teknologi Terapan, 2026)
Brake pads are generally manufactured using 60% asbestos. Although still widely used, asbestos is not environmentally friendly and poses serious health risks due to its carcinogenic properties, which can cause respiratory disorders when inhaled. Therefore, new environmentally safer innovations are needed, such as phenolic resin matrix composites. This study aims to analyze the effect of matrix percentage and compaction pressure on the density and hardness of phenolic resin matrix composites reinforced with aluminum, brass, silica sand, and boiler fly ash. The powder metallurgy method was applied, consisting of mixing, compaction, and sintering processes. Mixing was carried out using a horizontal ball mill with a Ball Powder Ratio (BPR) of 10:1 at 90 rpm for 4 hours. Matrix compositions of 25%, 29%, and 33% were tested, along with compaction pressures of 5100, 5400, and 5700 psi for 10 minutes. Density testing followed ASTM B962-17, and hardness testing used ASTM E110-14. The highest hardness before sintering was 154 HB, and the highest density was 1.308 g/cm³ at 5700 psi. After sintering, hardness increased to 216 HB and density to 2.120 g/cm³ at 5700 psi with 25% matrix composition.